Vinylogous michael addition of 3-alkylidene-2-oxindoles to beta,gamma-unsaturated alpha-keto esters by bifunctional cinchona alkaloids - Jaiswal, Manish K.; Kumar, Rajesh; Singh, Sanjay; Jain, Shailija; Vanka, Kumar; Singh, Ravi P. (European Journal of Organic Chemistry, 2020)
A highly enantioselective vinylogous Michael addition of 3-alkylidene-2-oxindoles with beta,gamma-unsaturated alpha-keto esters using a bifunctional tertiary-amine thiourea catalyst is demontsrated. The challenging Michael reaction with the beta,gamma-unsaturated alpha-keto esters has been accomplished due to the synchronized H-bond guided dual activation of vinylogous nucleophile and electrophile by catalyst. The reaction afforded product in high yield while resulting in excellent stereocontrol (> 19:1E/Zand upto 99 %ee).
Keywords: 3-Alkylidene-2-oxindoles; Asymmetric synthesis; beta; gamma-Unsaturated alpha-keto esters; Michael adduct; Vinylogous Michael addition